A Study on the Seismic Performance of Square and L-Shaped Buildings Resting on Various Angles of Hill Slopes - Poudel, Manaswi; Poudel, Manjari (AMC Indian Journal of Civil Engineering, 2021)
Due to the rapidly increasing population integrated with the problem of lack of availability of flat lands on hilly areas, the practice of constructing buildings on sloping grounds is increasing. This research aims to analyze the similarities and differences in the performance of L-shaped and square plan buildings resting on sloping grounds that are subjected to earthquake induced lateral forces. In order to achieve the objective, we modeled a total of 14 buildings, seven of which are of square plan, and remaining are L-shaped. The buildings are placed at hill slope angles ranging from 0 to 30 degrees. These buildings are analyzed using Response Spectrum Method in a structural analysis software called ETABS. A comparative analysis of the seismic parameters such as time period, base shear, modal mass participation and displacement is made for all L-shaped and square plan buildings and presented in the paper.